Band gap tuning and applications of ZnO nanorods in hybrid solar cell: Ag-doped verses Nd-doped ZnO nanorods. (April 2019) - Saboor, Abdus; Shah, Syed Mujtaba; Hussain, Hazrat
Abstract: ZnO nanorods doped with different concentrations of Ag and Nd (1–7%) were synthesized by hydrothermal method. In this article we describe the synthesis, characterization and applications of pristine ZnO, Ag-doped ZnO and Nd-doped ZnO nanorods in hybrid bulk heterojunction solar cells. Their optical, structural, and morphological properties were analyzed by using UV–Visible spectroscopy, X-ray diffraction (XRD), Scanning electron microscopy (SEM), and Energy dispersive X-ray spectroscopy (EDX). The X-ray diffraction analysis reveals that the pristine and doped ZnO nanorods were crystallized in a hexagonal wurtzite structure. SEM images supplemented with EDX were used to explore the morphology, size and chemical composition of pristine ZnO, Ag-doped ZnO and Nd-doped ZnO samples. UV visible absorption spectra showed that bathochromic shift occurred when ZnO nanorods were doped with Ag and Nd up to a certain limit of dopant concentration. Doped ZnO nanorods were found more conducting than prisitne ZnO nanorods. This work also represents the chemical modification of pristine ZnO, Ag-doped ZnO, and Nd-doped ZnO nanorods with a bromopyrogallol red dye (Br-PGR) which is not reported yet. The pristine and doped samples were sensitized with Br-PGR and the material so sensitized was tested in solar cell. The optical properties of grafted samples were thoroughly studied by using UV–visible spectroscopy. The Nano-hybrid material was tested as a photoactive blend of the DSSCs and their current-voltage measurements (I-V) were performed to examine the effect of pristine and doped ZnO nanorods on the performance of solar cells. Moreover current voltage (I-V) measurements confirmed the boosting of efficiency in pristine and doped ZnO nanorods based DSSCs owing to their sensitization with Br-PGR. Maximum power conversion efficiency of 1% was recorded for Ag-doped ZnO nanorods.